TYPES OF MAXILLARY TUMOURS AND THE RESULTING POST-SURGICAL DEFECTS IN PATIENTS AT A TEACHING HOSPITAL - Murad, Nida; ., Zakirullah; Ghani, Fazal (Journal of Postgraduate Medical Institute, 2011)
Objective: To report the frequency of the types of maxillary tumours and the resulting post-surgical defects Methodology: A pre-structured proforma was used for data collection. Data recorded included patients' age, gender, type of maxillary tumour, type of maxillectomy and approach for resection, Post-surgical defect based on Aramany classification for acquired maxillary defects, neck dissection, radiotherapy, and prosthetic rehabilitation. Data were computed for descriptive statistics including frequencies, percentages and mean values. Results : Patients (n=53) had a male to female ratio of 1.7. Some 26.4% patients belonged to the age group of 31-40 years. Maxillectomy was done for inverted papilloma, a benign tumour in 1.9% patients as compared to malignant squamous cell carcinoma in 66% patients. Maxillary resection for fibrous dysplasia was done in 3.8% patients who were relatively younger.. Maxillectomy in all cases was performed using Weber-Fergusson incision approach. Surgical resection resulted in Armanay class I defect in 73.58% patients. In 92.5% patients a surgical obturator was provided to patients at the time of maxillectomy. Conclusion : Maxillectomy was mainly performed for resecting malignant tumours using Weber-Fergusson incision with the fitting of immediate surgical obturator. The resulting defect was mainly Aramany Class I defects. based on Aramany classification. Study design, duration and setting: This descriptive study was done during the period of 5 years (2005-11) at the Otorhinolaryngology & Head and Neck Surgery Unit, Khyber Teaching Hospital Peshawar.